The provincial influence and paradiplomacy of Yunnan and Guangxi within the belt and road initiative in Southeast Asia - Ong, Zhen Zhen (Nanyang Technological University, 2022)
Most interpretations of the Belt and Road Initiative (BRI) are premised on the assumption that China is a unitary foreign policy actor and the BRI is a coherent, centrally-led grand strategy aimed at achieving the nation’s geopolitical and strategic goals. This essay challenges this conventional wisdom by applying Liu and Song’s three dimensions of international actorness to examine how Yunnan and Guangxi conduct paradiplomacy and influence the formulation and implementation of the BRI within Southeast Asia. By illustrating the means at which both provinces lobby the central government and engage in the conduct and management of their foreign relations, this essay analyses the dual presence of internal and external provincial agency, respectively. Recognising the competitive dynamics between Yunnan and Guangxi, this paper further discusses the implications of interprovincial competition on the BRI’s reception in Southeast Asia.